The stability of Islamic finance : creating a resilient financial environment for a secure future - Askari, Hossein (Wiley finance, 2010)
The book's main focus is on the question of the sources of financial instability which seems inherent in the conventional system. As a core component of this focus, the book will consider episodes of turbulence and instability in a historical context recalling the occurrence of such events from mid-19th century to the present